Efficiency of insecticides against the sucking phyllophages in apple orchards on drip irrigation in the Eastern Forest-Steppe of Ukraine - Vasyliev, S. V. (The Kharkiv Entomological Society Gazette, 2022)
The effect of insecticides on the main pests of apple leaves has been studied. Nine species of phyllophagous insects have been identified. The green apple aphid (Aphis pomі (De Geer, 1773)) and the apple leaf midge (Dasineura mali (Kieffer, 1904)) were of economic importance. Insecticides of different chemical classes (neonicotinoids and ketoenols) were used against the pests. The studied chemical preparations had a high protective effect against the aphids and the gall midge larvae. Movento 100SC, CS (2.0 l/ha) was the most effective insecticide, it had a technical efficiency ranges from 92.6 to 100.0% against the aphid and 86.5–99.1% against the gall midge larvae. The effect of insecticides on the pests varied by year and apple variety. The following averaged data on technical efficiency against the aphid have been obtained: Mospilan, SP (0.3 kg/ha) — 83.3–100.0%, Tamer, SP (0.3 kg/ha) — 90.0–96.4%, Koginor, SL (0.3 l/ha) — 91.3–98.5%, Konfidor 200 SL (0.3 l/ha) — 91.4–97.1%. These insecticides was effectively of 81.1–98.2, 88.9–97.8, 82.8–97.0, and 83.3–97.1% respectively against the larvae of the apple leaf gall midge. 3 figs, 6 tabs, 25 refs.